REMOTE HEALTH MONITORING USING WIRELESS BODY AREA NETWORK (WBAN) - GOI, CHEN SHEN (IRC, 2019)
In the recent research conducted by World Health Organization, by the year of 2020, the number of people aged 65 or older will outnumber children age of 5 or younger for the first time since the beginning of recorded history [1]. Therefore, more of the world population would be left vulnerable to disease and are in need of constant health monitoring once they grew older. Hence, in this paper focuses on building a working wireless health monitoring system which could help this situation. This research study includes development of a health monitoring hardware to obtain sensory data from human body which could be sent wirelessly to the cloud. There are a few important aspects that are vital to this system which are the sensors, microcontroller, wireless architecture and database server. The system design proposed in this research starts from the sensor data collection. The sensors that are used in this research are pulse sensor for heart beat monitoring and temperature sensor lm-35 for body temperature monitoring. Both the sensors will have Arduino Uno to act as their microcontroller for data collection. Both microcontrollers will send the obtained data to the master microcontroller that has Wi-Fi shield connected to it. The master microcontroller will then relay this data to the database server or cloud for storage and visualisation. The cloud platform is used is Thingspeak as it is a free database server with MATLAB compatibility.